(3GdJbfjGJ GdHfcjI hYedjGJ GdGFJeGf (B/s - (3fGUQ, SdjeGfs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2015)
(3JfGhd gPG GdcJGH GdJbfjGJ GdHfcjI hYedjGJ GdEFJeGf, hJJeKd eMGhQg GdcHQi aj eGjdj(B: (3eONd YGe Gdi GdJbfjGJ hGdNOeGJ GdHfcjI hYedjGJ GdGFJeGf Hcd HeNJda CfhGYgG (B((3bUjQ, eJhSW hWhjd GdCLd(B) . (3JbfjGJ heYGjjQ Jbjje GdeTGQjY hgj GdJj jMJGLgG ehXa GdHfc aj OQGSI Cj eTQhY jWdH bQVG Ch JehjdG(B. (3JbfjGJ Jehjd GdJLGQI GdNGQLjI , hCNjQG YedjGJ GdHfhc GdESdGejI (B. s
(3GdeQGLY U(B.168s
Keywords: (3GdGFJeGfs; (3GdHfhcs; (3GdHfhc GdESdGejIs